Effect of storage tank material on biodiesel stability under different environmental conditions - Mohd Zini, Nurul Hilwa; Shikh Anuar, Fadhilah; Saadun, Mohd Noor Asril; Mohamed Nor, Mohd Khairi; Yaakob, Mohd Yuhazri; Narasimmanaidu, Satishwara Rao (Malaysian Tribology Society, 2023)
This study aimed to determine the effect of storage tank materials on fuel storage stability under different environmental conditions. Experiments on biodiesel blends (B10) were conducted using semi-transparent HDPE, clear glass, and stainless steel with various storage shapes under sun-exposed outdoor condition (28-32°C) and enclosed indoor condition (25-27°C) for 180 days. Oil samples from selected storage materials were monitored and the values of density, viscosity, acid value, flashpoint, and water content were recorded. In this study, the effect of storage tank material and environmental conditions were significant on biodiesel stability; oil samples placed indoor without exposure to sunlight recorded slight increase in data, regardless of storage material, while samples stored outdoor in clear glass containers showed a dramatic increase in viscosity, density, acid value, and water content by 23.7%, 9.7%, 150.4%, and 221.3%, respectively within 180 days of storage. Meanwhile, the flashpoint decreased by 6.58% with increasing storage duration. It also can be observed that discolouration was more rapid in glass storage tank compared to HDPE and stainless-steel tanks. From this study, it can be concluded that stainless steel is recommended as storage material due to its versatility to degradation for lower biodiesel blends.